Harvard business review on the mind of the leader (Harvard Business School Press, 2005)
How do leaders view themselves? What thought processes govern their actions? In this insightful book, renowned leadership experts, including Warren Bennis and Daniel Goleman, probe the fascinating psychology of leadership. From the impact of narcissism on leaders' effectiveness to the crises and challenges that each stage of leadership brings, this book helps leaders gain a deeper understanding of their complex role.